스마트 모빌리티를 위한 경로변경이 가능한 스마트 셔틀 운행기법 연구 - 정성욱(Sung-Wook Chung); 강용수(Yong-Su Kang); 손영훈(Yeong-Hun Son) (한국정보전자통신기술학회 논문지, 2020)
With the development of the 4th Industry Revolution and the progress of related technologies, people have been using various services in a more convenient way in their daily lives. Among these technologies, the smart mobility is a service that effectively transports people or packets from the origin to the final destination using a variety of methods/vehicles. With respect to the smart mobility technology, the shuttle service is operational at the final destination. The conventional shuttle operation only takes into account the shuttle operability and does not consider the shuttle-passenger efficiency at all by the one-way routing. Therefore, in this paper, we propose the smart shuttle algorithm that can change the routes to efficiently support boarding passengers. Our proposed scheme consists of 3 algorithms: the shuttle operating algorithm, the re-routable shuttle traveling algorithm, and the passenger-riding algorithm. All those 3 algorithms are effectively co-operated and collaborated for better performance. In-depth experiments were conducted to analyze and to show the superior performance, resulting in an average 23.6% reduction of destination-arrival time per passenger, average 10.37% reduction of shuttle-waiting time per passenger, and average 15.38% decrease of shuttle traveling time per hour. This proves that our smart shuttle traveling scheme reveals the whole remarkable performance, effectively using the re-routable characteristics. 4차 산업의 발달과 관련 기술의 발전으로 사용자들은 보다 다양한 서비스를 보다 편리한 방법으로 일상생활에서 사용하고 있다. 이러한 기술 중 스마트 모빌리티(Smart Mobility) 기술은 출발지에서 최종 목적지까지 다양한 방법을 이용하여 효과적으로 이동 및 운송하는 서비스로 단계별 운송수단의 활용(Multi-Modal Service), 효과적인 운송수단의 공유 등의 방법을 통해 보다 사용자들이 해당 서비스를 사용하고 있다. 이러한 스마트 모빌리티 기술 중 최종 목적지 도착단계에서 셔틀(Shuttle)을 이용할 수 있는데, 기존 셔틀 운행방법은 운행회사의 운용성만 고려한 방법으로, 일정한 한 방향으로만 주기적으로 운행하는 방법으로 운행함으로써 셔틀 탑승객의 효율성을 전혀 고려하지 않고 있는 방법이다. 따라서 본 연구에서는 스마트 모빌리티를 지원하는 경로변경이 가능한 스마트셔틀 운행기법을 제안하고자 한다. 제안하는 기법은 셔틀운행 알고리즘, 셔틀 경로변경 알고리즘, 승객 셔틀탑승 알고리즘의 3가지로 구성되며 각각의 알고리즘들이 유기적이고 효과적으로 작동하여 기존 방법보다 우수한 성능을 보여준다. 스마트 셔틀기법의 효과적인 성능분석을 위하여 심도있는 실험(Extensive Experiments)을 수행하였으며, 해당 실험을 통해 승객별 평균 23.6%의 목적지 도착시간 감소, 승객별 평균 10.37% 탑승 대기시간 감소, 그리고 시간당 평균 15.39% 셔틀 이동거리 단축의 성능향상을 보여준다. 이는 탑승자를 고려한 스마트 셔틀기법이 효과적인 경로변경을 통하여 기존 방법보다 보다 우수한 성능을 제공하고 있음을 입증한다.